Pharmacokinetic and pharmacodynamic effects of 2 registered omeprazole preparations and varying dose rates in horses. (19th December 2020) - Wise, Jessica C.; Hughes, Kristopher J.; Edwards, Scott; Jacobson, Glenn A.; Narkowicz, Christian K.; Raidal, Sharanne L.
Abstract: Background: Omeprazole preparations vary in bioavailability in horses. Hypothesis/Objectives: To characterize the pharmacokinetics and pharmacodynamics of an existing enteric‐coated oral omeprazole paste (REF) and a novel, in‐feed, enteric‐coated dry granule preparation (NOV). Animals: Twelve Standardbred/Thoroughbred mares free from clinical disease. Methods: A prospective, blinded randomized interventional study was trial, conducted in 3 parts: (a) bioavailability study, (b) dose titration study, and (c) comparative clinical pharmacodynamic study, each using a blocked crossover design. Results: Consistent with the larger dose administered, C max (median, 1032 ng/mL; range, 576‐1766) and AUC0‐24 (median, 63.9 μg/mL*min; range, 42.4‐152.4) were greater after single oral administration of NOV than REF (282.7 ng/mL; range, 94.8‐390.2, and 319 23.8 μg/mL*min; range, 8.2‐42.3, respectively; both P = .004). No differences were observed between products for absolute oral bioavailability (NOV 55% range, 15‐88; REF 17% range, 10‐77; P = .25). Treatment with both preparations was associated with reduced gastric squamous ulcer scores and increased pH of gastric fluid. Bioequivalence was demonstrated for pharmacodynamic measures with the exception of % time pH <4, despite differences in dose rate and subsequent plasma omeprazole concentrations. Conclusions and Clinical Importance: The findings of this study indicate that the NOV product would be a suitable alternative to the reference product, and confirm that plasma concentrations of omeprazole and omeprazole dose do not predict drug pharmacodynamics in horses.